"Celestial Epicurisme": John Locke and the Anglican language of pleasure, 1650–1697. Issue 2 (4th March 2022) - Chatterjee, Jacob Donald
ABSTRACT: This article presents a new understanding of how Anglican clergymen and writers remoulded common notions of the moral status of pleasure during the latter half of the seventeenth century. It addresses the current historiographical neglect of the philosophical content of ethical thought within the Church of England. For Anglican thinkers developed innovative moral arguments about the rational order of human satisfactions in order to direct the disruptive appetites towards good ends. This article illustrates the conceptual trajectory of this ethical discourse by comparing John Locke's developing moral ideas with those of Robert South, Public Orator at Oxford after 1660, and Samuel Parker, Bishop of Oxford after 1686. For the course of Locke's shifting ethical thought reflected a philosophical movement within an Anglican language of pleasure, from South's moderate position – that pleasure was a significant good among other ends – to Parker's radical stance – that goodness was reducible to that which was delightful.